(untitled) (Damascus University Journal for engineering sciences, 2024)
The use of non-ceramic insulation materials in the fields of electrical engineering in general and in the field of high voltage engineering in particular is increasing because of the good mechanical properties of these materials, which qualified them to be an alternative to glass insulators and porcelain. As electronic accelerators increased and developed, radiotherapy of polymers began to produce good results in networking processes. This is by forming cross-linking between the chains of its giant molecules, which helps to improve a number of mechanical properties of these materials. This work aims to research the improvement of the mechanical properties of polyphenol chloride materials using irradiation processes. Similar and frequent polyphenol chloride samples were manufactured and then radiotherapy by gamma rays to achieve the networking process. The change in their mechanical properties was studied before and after irradiation, and the most important findings in this research will be reviewed.